2017
DOI: 10.31219/osf.io/4rvns
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Determining optimal parameters of the Self Referent Encoding Task: A large-scale examination of self-referent cognition and depression

Abstract: This is a post-print of a manuscript which has been published in Psychological Assessment.Although the Self-Referent Encoding Task (SRET) is commonly used to measure self-referent cognition in depression, many different SRET metrics can be obtained. The current study used best subsets regression with cross-validation and independent test samples to identify the SRET metrics most reliably associated with depression symptoms in three large samples: a college student sample (n = 572), a sample of adults from Amaz… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…The primary behavioral outcome from the SRET is the probability of endorsing positive vs. negative words, which we have demonstrated to be strongly linked to depression (Dainer-Best et al, 2018). Additionally, including an extra subset of words at each time-point allowed us to distinguish between responses that varied due to repetition and those that varied putatively due to changes in self-referential processing.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The primary behavioral outcome from the SRET is the probability of endorsing positive vs. negative words, which we have demonstrated to be strongly linked to depression (Dainer-Best et al, 2018). Additionally, including an extra subset of words at each time-point allowed us to distinguish between responses that varied due to repetition and those that varied putatively due to changes in self-referential processing.…”
Section: Methodsmentioning
confidence: 99%
“…The relationship between negative self-schema and the maintenance of depression is sometimes viewed in causal terms, with stronger negative self-schemas thought to produce a more protracted episode of depression (Beck, 1967). It is clear that both positive and negative schema are strongly correlated with depressive symptoms (Phillips et al, 2010; Dainer-Best et al, 2018), and can predict worsening of symptoms (Disner et al, 2016); however, such studies are correlational and thus vulnerable to third variable explanations that account for the association between self-referent processing and depression.…”
Section: Introductionmentioning
confidence: 99%
“… Data are located on the Texas Data Repository, https://doi.org/10.18738/T8/XK5PXX (Dainer-Best et al, 2017) and additional information on Github, https://jdbest.github.io/sretmodels/. An interactive Shiny interface to explore the relationships between these variables can be viewed online at https://jdbest.shinyapps.io/shiny-comparisons/ …”
mentioning
confidence: 99%
“…Although there are no previously published studies examining the prediction of day-to-day fluctuations in depression by the SRET, prior cross-sectional work suggests a strong association between endorsements of negative adjectives on the SRET and depression severity (rs ranged from .65 to .70-a large effect size; Dainer-Best, Lee, et al, 2018). Based on this evidence, we reasoned that large effects may also be observed in the current study.…”
Section: Sample Size Justificationmentioning
confidence: 47%
“…Many cross-sectional studies provide evidence of an association between negative self-referent thinking and depression. For instance, depressed people are more likely than non-depressed individuals to endorse negative adjectives (e.g., defective, worthless, dumb) as self-descriptive (Dainer-Best, Lee, et al, 2018;Dalgleish et al, 2004;Sarsam et al, 2013). A recent meta-analysis found that depressed individuals endorsed more negative adjectives as self-descriptive than non-depressed individuals.…”
Section: Introductionmentioning
confidence: 99%